2018
DOI: 10.1002/adfm.201705928
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain‐Tunable Microwave Magnetism in Flexible CuFe2O4 Epitaxial Thin Film for Wearable Sensors

Abstract: Purely mechanical strain-tunable microwave magnetism device with lightweight, flexible, and wearable is crucial for passive sensing systems and spintronic devices (noncontact), such as flexible microwave detectors, flexible microwave signal processing devices, and wearable mechanics-magnetic sensors. Here, a flexible microwave magnetic CuFe 2 O 4 (CuFO) epitaxial thin film with tunable ferromagnetic resonance (FMR) spectra is demonstrated by purely mechanical strains, including tensile and compressive strains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 44 publications
(44 reference statements)
1
56
0
Order By: Relevance
“…Very recently, intensive research has been devoted to such epitaxial growth of functional perovskite and spinel oxides films on mica for flexible devices . For perovskite SrRuO 3 film system, the crystallographic orientation relationship between films and mica substrate was determined as {111} films || (001) mica and 〈011true¯〉 films || [010] mica by X‐ray diffraction (XRD) .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, intensive research has been devoted to such epitaxial growth of functional perovskite and spinel oxides films on mica for flexible devices . For perovskite SrRuO 3 film system, the crystallographic orientation relationship between films and mica substrate was determined as {111} films || (001) mica and 〈011true¯〉 films || [010] mica by X‐ray diffraction (XRD) .…”
Section: Introductionmentioning
confidence: 99%
“…For flexible spintronics based applications, magnetic materials with high spin polarization as well as excellent mechanical flexibility are highly desirable to meet the requirement of high performance and stability . In the previous studies, bending‐deformation‐related magnetic hysteresis (M‐H) loops have been found in several flexible epitaxial oxide thin films with high crystalline quality, such as CoFe 2 O 4 , CuFe 2 O 4 , LiFe 5 O 8 , Fe 3 O 4 , etc. The results indicate that the effects of bending‐induced mechanical strains on the magnetic properties are different for different materials.…”
mentioning
confidence: 99%
“…22 In this context, the integration of magnetic materials on mica is also gaining importance. [23][24][25][26] In parallel, the interest in magnetic 2D materials has been spurred by the recent discovery of this property, either intrinsic or associated to defects, in some of this low dimensional systems. 27,28 Despite the relevance of mica as substrate for growing magnetic materials, not enough attention has been paid to the magnetic properties of mica itself.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it has increasingly been the substrate of choice for the development of new functional materials. 26,[37][38][39] Yet, the fundamental understanding of this fluorine-rich silicate is far from complete. This is particularly true concerning the magnetic properties which, to our knowledge, were only qualitatively studied by Tsui et al 40 on the fluoromica samples prepared in their laboratory to be used as substrates to grow rare earth films.…”
Section: Introductionmentioning
confidence: 99%